Penanaman Sikap Tanggung Jawab dan Kedisiplinan Peserta Didik melalui Pendidikan Kewarganegaraan - Ani Sulianti; Nurul Saila; Dzaky Isyuniandri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine: 1. The role of civic education in instilling the responsible attitude of students, 2.The role of civic education in instilling disciplinary attitudes in students. This type of research is a descriptive study with a qualitative approach, research subjects are students in SMP Negeri 2 Kunir. The results showed that: 1. Citizenship education has a very important contribution in instilling the attitude of responsibility towards students through learning materials, guidance and direction from the teacher and the direction of daily activities outside the classroom to be able to develop the attitude of social responsibility 2. Education Citizenship has an important role in instilling moral values of discipline toward students through the learning process in shaping attitudes and behavior that obeys the rules that apply both within the school and in the community.